2009
DOI: 10.1080/01421590802637974
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of a pediatric mock code program at a children's hospital

Abstract: Background: Pediatric cardiopulmonary arrests are rare. Mock codes were instituted to bridge the gap between opportunity and reality. Aim: The goal was to improve medical caregivers' skills in pediatric resuscitation. Methods: All pediatric and internal medicine/pediatric (med/peds) residents were anonymously surveyed pre-and postintervention about confidence level about codes and code skills. Twenty mock codes were conducted during the 1 year intervention period. Statistical comparisons were made between each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 14 publications
3
31
0
Order By: Relevance
“…Although IO placement is discussed in all PALS courses and is considered easy to learn, we found our residents were not confident with this important procedure. 11 Gaies et al 12 found similar findings when surveying pediatric program directors. More than 60% of program directors felt IO placement was a very important skill, but just over 20% felt their graduating residents were competent to perform IO placement.…”
Section: Skill Index With and Without Mock Codessupporting
confidence: 63%
See 4 more Smart Citations
“…Although IO placement is discussed in all PALS courses and is considered easy to learn, we found our residents were not confident with this important procedure. 11 Gaies et al 12 found similar findings when surveying pediatric program directors. More than 60% of program directors felt IO placement was a very important skill, but just over 20% felt their graduating residents were competent to perform IO placement.…”
Section: Skill Index With and Without Mock Codessupporting
confidence: 63%
“…8-10 However, we 11 have reported that even bimonthly in situ mock codes did not lead to individual resident learning; instead they highlighted system problems. Based on these results, our current study sought to improve individual resident confidence and performance in managing pediatric code events and performing procedures on critically ill patients.…”
mentioning
confidence: 99%
See 3 more Smart Citations